Fractional ethanol precipitation modulates the structure and function of Coprinus comatus mycelial polysaccharides: alleviation of DSS-induced injury in Caco-2 cells via regulation of mitochondrial function - Chen, Ruijie; Gu, Tao; Xiang, Zhun; Wei, Shaofeng (Frontiers in Nutrition, 2026)
IntroductionThis study aimed to systematically fractionate Coprinus comatus mycelial polysaccharides using ethanol precipitation, screen the optimal fraction, and investigate its potential to alleviate inflammation in a dextran sulfate sodium (DSS)-induced Caco-2 cell model.MethodsPolysaccharides (CCPJ-40, -60, -80) were obtained with 40%, 60%, and 80% ethanol. Their chemical properties (yield, monosaccharide composition, molecular weight) and in vitro bioactivities were assessed. The optimal fraction was investigated in a dextran sulfate sodium (DSS)-induced Caco-2 cell model.ResultsThe results revealed that the ethanol concentration significantly affected the polysaccharide yield, chemical composition, and bioactivities. Notably, CCPJ-80 exhibited the highest yield and total sugar content. Monosaccharide composition analysis indicated that both CCPJ-40 and CCPJ-80 were composed of L-fucose, L-arabinose, galactose, glucose, xylose, mannose, ribose, and D-glucuronic acid, whereas CCPJ-60 additionally contained rhamnose. Regarding molecular weight distribution, CCPJ-40 had a high molecular weight and was relatively polydisperse, while CCPJ-60 and CCPJ-80 had lower molecular weights with good homogeneity. In the in vitro activity assessment, CCPJ-80 demonstrated the most potent antioxidant and prebiotic activities. Further cell experiments confirmed that CCPJ-80 effectively alleviated the DSS-induced inflammatory state in Caco-2 cells. The underlying mechanisms included significantly reducing the levels of lactate dehydrogenase, tumor necrosis factor-α, interleukin-6, reactive oxygen species, and mitochondrial ROS, while simultaneously enhancing superoxide dismutase activity and restoring the mitochondrial membrane potential.DiscussionThis study elucidates the regulatory effect of ethanol precipitation concentration on the physicochemical properties and functional activities of CC mycelial polysaccharides, and reveals the potential of CCPJ-80 to ameliorate ulcerative colitis by modulating oxidative stress and mitochondrial function pathways, providing a scientific basis for developing CCPJ as a functional food or therapeutic agent.